Historia wizualna Zielonej Góry spisana kamerą Sky Piastowskie = The visual history of Zielona Gora through the lens of the Sky Piastowskie film group - Domke, Radosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article explores the visual history of Zielona Gora as captured by the Sky Piastowskie film group. While providing biographical details about the group and general references to the films` narratives, the primary focus is on illustrating the evolving image of the city on film. The analysis centres on three productions: "Że życie ma sens" [That Life Makes Sense], "Dzień w którym umrę" [The Day I Die], and "8 w poziomie" [Horizontal 8]. This innovative approach provides a foundation for a more thorough understanding of the visual history of Zielona Gora and the Lubuskie Region in the future.
Keywords: historia wizualna; kinematografia; Zielona Góra; Sky Piastowskie; kino niezależne; kino amatorskie; visual history; cinematography; independent cinema; amateur cinema